Administration Workers Knowledge on First Aid - Kucharska, Ewelina Karolina (Journal of Education, Health and Sport, 2017)
Introduction and Aim Today, more and more emphasis is placed on training, awareness, change. People want to feel safe - this is one of the needs, according to the pyramid Maslow. To achieve this, training, knowledge acquisition and refinement are needed. Knowledge of the principles of first aid is important because it can save human life. Information about the scope of rescue and help we acquire in everyday life and in training, which aims to take care of the employee, the will to help, showing that everyone has the choice and influence on what they do, reaching people's awareness, imaging the threats and How to avoid them. The purpose of this paper is to analyze and estimate the level of knowledge and awareness about first aid among office workers. By showing what are the effective forms of training and how important first-aid skills are, I'm looking for answers as the average worker knows first aid, or should there be even more emphasis on training in the field. Material and Methods The research was conducted in the form of a questionnaire. Respondents who were administrative and office workers working in the city with over 100,000 inhabitants, in the city to 10,000 inhabitants and in the country, answered questions about their first aid knowledge. Results The results are presented in descriptive. After completing the survey, respondents answered specific questions. Conclusions The conclusion of the questionnaire replies is that there is too little first aid training, especially among rural and urban workers below 10 000 000 inhabitants.